Nanotribology of clean and oxide-covered silicon surfaces using atomic force microscopy - Moon, W; Contera, SA; Yoshinobu, T; Iwasaki, H (JJAP, 2000)
Atomic force microscopy (AFM) has been used for tribological studies of silicon surfaces both with and without an oxide layer on the surface. Three different types of surfaces were prepared: a silicon surface with a chemical oxide made by the SC1 process, a silicon surface with a thermal oxide, and a H-terminated silicon surface without an oxide layer. Only in the case of the chemical oxide, scratching of the oxide and ploughing of the silicon by the Si3N4 AFM tip were observed. On the other hand, no wear of the sample was noted on the other surfaces. On these surfaces, the AFM often produced elevated patterns in the shape of the scanned area, which were no longer visible after HF etching. The difference between the tribological behavior of the chemical-oxide-covered surface and that of the other surfaces is discussed in relation to the presence of hydroxyl groups in the oxide layer.